A review of recent strategies for acid mine drainage prevention and mine tailings recycling. (March 2019) - Park, Ilhwan; Tabelin, Carlito Baltazar; Jeon, Sanghee; Li, Xinlong; Seno, Kensuke; Ito, Mayumi; Hiroyoshi, Naoki
Abstract: Acid mine/rock drainage (AMD/ARD), effluents with low pH and high concentrations of hazardous and toxic elements generated when sulfide-rich wastes are exposed to the environment, is considered as a serious environmental problem encountered by the mining and mineral processing industries around the world. Remediation options like neutralization, adsorption, ion exchange, membrane technology, biological mediation, and electrochemical approach have been developed to reduce the negative environmental impacts of AMD on ecological systems and human health. However, these techniques require the continuous supply of chemicals and energy, expensive maintenance and labor cost, and long-term monitoring of affected ecosystems until AMD generation stops. Unfortunately, the formation of AMD could persist for hundreds or even thousands of years, so these approaches are both costly and unsustainable. Recently, two alternative strategies for the management of AMD and mine tailings are gaining much attention: (1) prevention techniques, and (2) mine waste recycling. In this review, recent advances in AMD prevention techniques like oxygen barriers, utilization of bactericides, co-disposal and blending, and passivation of sulfide minerals are discussed. In addition, recycling of mine tailings as construction and geopolymer materials to reduce the amounts of wastes for disposal are introduced. Highlights: Acid mine drainage (AMD) causes serious environmental problems around the world. AMD generation can continue for decades until sulfide minerals are exhausted. Remediation options are effective but unsustainable. Prevention techniques are of importance to overcome AMD problems sustainably. Recycling of mine tailings can help reduce the amounts of tailings for disposal.